METHODOLOGICAL FOUNDATIONS OF MODERN FUTUROLOGY (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
This article of the author talks about the methodological foundations of modernfuturology, in addition, it is said that the focus of futurology on applied research leads to the lossof its philosophical (historical-philosophical) foundations. The connection between the historicalsciences and futurology is necessary because reconstruction in history is the same as forecasting infuturology. It should be emphasized here that the gradation of methodology within the frameworkИзвестия НАН КР, 2023, №5 171of scientific knowledge into philosophical, scientific, concrete scientific and experimental is conditional, and it is impossible to create a biased deep scientific concept, bypassing its philosophicalfoundations. Therefore, it is not very appropriate to expand on the opposite sides of forecastingand theoretical futurology.
Keywords: futurology, forecast, concept, theory, practice, methodology, science, activity, universe.